(untitled) (The Research of Medical Science Review, 2025)
Background: A potentially lethal condition known as morbidly adherent placenta (MAP) is often linked to severe postpartum hemorrhage (PPH) and, in some situations, hysterectomy. Objective: To determine the prevalence of Morbidly Adherent Placenta in Previous Scar Methodology: This retrospective was carried out at the department of Obstetrics & Gynecology DHQ hospital lakki marwat. The study duration was one year from June 2023 to July 2024. A total of 200 patients were enrolled in our study by using WHO sample size calculator. All the data was collected in a specialized proforma designed for this study. The data was entered and analyzed using SPSS Version 24. Results: In the current study, totally 200 patients were enrolled. The mean age (SD) was 27.99 (6.11) years. The incidence of MAP in our study was 26 (13%). Out of these 26 MAP patients, the incidence Placenta accreta was 14 (7%), placenta increta was 6 (3%) and placenta percreta was 6 (3%). Amongst the 26 MAP patients, the incidence of single cesarean scar was 2(1%), double was 4 (2%), thrice was 8 (4%) and fourth was 12 (6%). Conclusion: Our study concludes that the prevalence of MAP was 13% in females with previous scars. MAP is an extremely rare disorder that is 10 times more common in women with a history of scar. Due to its shorter length and previously scarred uterus, placenta accreta was the most common kind of MAP.